2020
DOI: 10.1111/petr.13777
|View full text |Cite
|
Sign up to set email alerts
|

Initial posaconazole dosing to achieve therapeutic serum posaconazole concentrations among children, adolescents, and young adults receiving delayed‐release tablet and intravenous posaconazole

Abstract: Posaconazole is a broad‐spectrum antifungal used for prophylaxis and treatment of invasive fungal diseases. There are limited data on the optimal dosing, safety, and efficacy of the DRT and IV formulations in immunocompromised pediatric and adolescent patients. We describe our experience including dosing, plasma trough concentrations, safety, and tolerability. Plasma concentrations ≥.7 µg/mL were considered therapeutic for prophylaxis and ≥1.0 µg/mL for treatment. Fifty‐four patients (median age of 16 years) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, the median maintenance dose did not differ significantly between patients aged <6 and 6–12 years old in this study, although a higher trend is shown in patients <6 years old ( Figure 4 ). One possible explanation for the higher doses in patients <13 years is that patients in this group were dosed based on current available data versus patients 13 years and older who were dosed based on package insert recommendations ( Bernardo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the median maintenance dose did not differ significantly between patients aged <6 and 6–12 years old in this study, although a higher trend is shown in patients <6 years old ( Figure 4 ). One possible explanation for the higher doses in patients <13 years is that patients in this group were dosed based on current available data versus patients 13 years and older who were dosed based on package insert recommendations ( Bernardo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analytical range was 0.025–5.00 μg mL −1 . For the purpose of this study, plasma concentrations ≥0.7 μg mL −1 were considered therapeutic for prophylaxis and ≥1.0 μg mL −1 for treatment ( Bernardo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…8,186 Therefore, TDM is indicated for patient groups at risk of low exposure who are receiving prophylaxis with the new posaconazole tablet formulation (e.g. patients with cystic fibrosis, 187 presence of graft-versus-host disease, 10,181 drug-drug interactions including those on concurrent corticosteroids and proton pump inhibitors, 10,188 obese patients, 189,190 young children [191][192][193][194] and patients with gastrointestinal complications including diarrhoea 10,190,195,196 ).…”
Section: Question 2 What Are the Present Antifungal Tdm Targets Sampl...mentioning
confidence: 99%
“…Moreover, the results of direct comparisons of the activity of these two triazoles in vitro are somewhat contradictory, with some studies showing roughly equivalent activities but species-specific variations [11,12], whilst others suggested that posaconazole MICs were generally lower than isavuconazole MICs with the common agents of mucoromycosis [13,14]. Additionally, it remains to be determined whether reported MIC differences between posaconazole and isavuconazole with members of the Mucorales are clinically relevant, given that drug exposures in vivo are usually higher with isavuconazole than with posaconazole [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%